The Impact of Official Development Assistance on Economic Growth of Lao PDR - PHOMPADITH, Soulidone; HER, Pheng; PHONPRASITH, Bounthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to analyze the impact of Official Development Assistance (ODA) on the economic growth of Lao PDR by using the time series data from 2000–2023 and implied with the OLS robust model where the dependent variable is gross domestic product, the main variable is official development assistance, and the control variable consists of foreign direct investment and inflation. The results of the analysis found that ODA has a positive effect on the economic growth of Lao PDR with a statistical significance level of 0.01. But after adding the control variable, ODA is not statistically significant; only the foreign direct investment variable has a positive effect with a statistical significance level of 0.01. While ODA and inflation are not statistically significant, foreign direct investment affecting economic growth in the same direction means that if other factors are constant, when foreign direct investment increases by 1%, the Lao PDR's economic growth increases by 0.538%, and vice versa, if foreign direct investment decreases by 1%, it will cause the Lao PDR's economic growth to decrease by 0.538%.